ANALISIS LAMA KAMBUH PASIEN HIPERTENSI DENGAN SENSOR TIPE III MENGGUNAKAN REGRESI COX KEGAGALAN PROPORSIONAL (Studi Kasus di RSUD Kartini Jepara) - Ishlahul Kamal; Triastuti Wuryandari; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Hypertension is a disease that silently kills the patients because they do not realize that they get hypertension until they check their blood pressure. It is important for hypertensive patients to know the factors that lead to the relapse time. To determine the relationship between the relapse time on hypertensive patients with the influencing factors is using regression analysis, the dependent variable is the failure time so to determine the relationship is using regression Cox proportional hazard. This research uses the medical records of hypertensive patients in period January to December 2014 in RSUD Kartini Jepara. The results indicate that the factors which affect relapse time of hypertension are kidney disease and stroke. The hypertensive patients that also suffer from kidney disease have relapse time sooner than patients who do not suffer from kidney disease. The hypertensive patients that also suffer from stroke have relapse time sooner than patients who do not suffer from a stroke. Keywords: Hypertension, Survival Analysis, Regression Cox Proportional Hazards